Disproportionate cancer worries in ultra‐short‐segment Barrett's esophagus in Japan - Sho Fukuda; Kenta Watanabe; So Takahashi; Tatsuki Yoshida; Shusei Fujimori; Taiga Komatsu; Yosuke Shimodaira; Tamotsu Matsuhashi; Katsunori Iijima (DEN Open)
Abstract Objectives Although Barrett's esophagus (BE), especially ultra‐short‐segment BE (USSBE), is very frequently diagnosed in Japan, how subjects feel about receiving a diagnosis of BE is unclear. We therefore prospectively investigated cancer worry in subjects who received a BE diagnosis. Methods Self‐administered questionnaires were sent to subjects who were diagnosed with BE at three health checkup institutes in Akita Prefecture, Japan. The cancer worry scale (CWS) was used to quantitatively assess the fear of developing cancer. The BE subjects were classified into USSBE <1 cm and non‐USSBE ≥1 cm groups. Factors associated with the CWS were investigated using logistic regression analyses. Results A total of 325 (31%) subjects, comprising 229 USSBE and 96 non‐USSBE patients were included in this study. Compared with the USSBE group, the non‐USSBE group had a significantly higher frequency of a history of a BE diagnosis and perception of carcinogenesis. However, the CWS was similar between the USSBE and non‐USSBE groups, with a median CWS of 12.5 (3.75) versus 12.7 (3.65). A multivariate logistic regression analysis revealed that while positive reflux symptoms were significantly associated with a positive CWS, the BE length was not significantly associated with it, with an odds ratio (95% confidence interval) of 1.3 (0.75–2.2). Conclusions A BE diagnosis promotes a similar level of worry about cancer among subjects, irrespective of the length of BE. In Japan, since USSBE poses a much lower cancer risk than non‐USSBE, the former may frequently be associated with a disproportionate cancer worry relative to the latter. (UMIN000044010)